Positive End-expiratory Pressure Redistributes Regional Blood Flow and Ventilation Differently in Supine and Prone Humans - Petersson, Johan; Ax, Malin; Frey, Joana; Sánchez-Crespo, Alejandro; Lindahl, Sten G. E.; Mure, Margareta (Anesthesiology (Philadelphia), 2010)
Animal studies have demonstrated an interaction between posture and the effect of positive end-expiratory pressure (PEEP) on regional ventilation and lung blood flow. The aim of this study was to explore this interaction in humans. Regional lung blood flow and ventilation were compared between mechanical ventilation with and without PEEP in the supine and prone postures. Six normal subjects were studied in each posture. Regional lung blood flow was marked with In-labeled macroaggregates and ventilation with Technegas (Tc). Radiotracer distributions were mapped using quantitative single-photon emission computed tomography. In supine subjects, PEEP caused a similar redistribution of both ventilation and blood flow toward dependent (dorsal) lung regions, resulting in little change in the V/Q correlation. In contrast, in prone subjects, the redistribution toward dependent (ventral) regions was much greater for blood flow than for ventilation, causing increased V/Q mismatch. Without PEEP, the vertical ventilation-to-perfusion gradient was less in prone postures than in supine, but with PEEP, the gradient was similar. During mechanical ventilation of healthy volunteers, the addition of PEEP, 10 cm H2O, causes redistribution of both lung blood flow and ventilation, and the effect is different between the supine and prone postures. Our results suggest that the addition of PEEP in prone might be less beneficial than in supine and that optimal use of the prone posture requires reevaluation of the applied PEEP.